The inspirational effect of sporting achievements and potential role models in football: a gender-specific analysis. Issue 5 (2nd September 2016) - Wicker, Pamela; Frick, Bernd
Abstract : This study examines the trickle-down effect of potential role models and sporting achievements, respectively. Specifically, we look at the inspirational effect of same-sex and opposite-sex role models on male and female participation in German amateur football. Longitudinal data on club memberships and amateur teams were collected for 21 regional football associations over a 15-year-period. The results of panel regression models show that the achievements of the 2006–2010 male national teams have a significant positive effect on the number of female club memberships and teams, supporting the notion of gendered heroism. Yet, male achievements in 2002 have a negative effect. Thus, sporting success does not automatically lead to the development of positive role models and inspirational effects, indicating that other factors (e.g. age, personality, and style of play) may play a role as well. Sporting achievements of female teams have no measurable inspirational effect on both male and female participation.